Effect of Sub-Inhibitory Wastewater Stressors on Mutation Frequency in Clinically Relevant Aeromonas Species - (:unkn) unknown (My University, 2023)
Antimicrobial resistance among pathogens is steadily increasing resulting in untreatable infections and elevated mortality rates, with an estimation of claiming 10 million lives worldwide by 2050. A common factor accelerating resistance is the presence of sub-inhibitory microbial stressors (e.g. antimicrobials, heavy metals, and disinfectants), which can drive horizontal gene transfer and mutagenesis in various environments. Improper disposal of pharmaceuticals, excretion of antimicrobial byproducts from humans and livestock, and excess storm runoff are common sources of these pollutants. An environmental reservoir rich in stressors and bacterial populations, including the emerging pathogen Aeromonas, is wastewater. Our objective in this study was to determine the mutagenic impact of sub-lethal concentrations of wastewater, common antimicrobial contaminants, and wastewater disinfectants amongst residential wastewater bacterial populations. Fluctuation assays were performed to quantify mutation frequencies in environments with these pollutants. Briefly, clinically relevant bacterial cultures of A. hydrophila and A. caviae were incubated with various stressors for 24 hours with subsequent plating on tryptic soy agar containing eight times the MIC value of rifampin. For each treatment group evaluated, sixteen or more independent experiments were included. Mutation frequencies were determined by dividing resistant colonies by total colonies on tryptic soy agar without antibiotic. In all, sub-lethal concentrations of wastewater influent, four antibiotics (i.e., ciprofloxacin, tetracycline, trimethoprim, and cefotaxime) each with different molecular targets, and common wastewater disinfectants (i.e. ultraviolet light and calcium hypochlorite) were assessed for their role on accelerating mutagenesis. Our findings showed that filtered influent wastewater increased mutagenic evolution by 3-fold within A. caviae. When looking at the impact of sub-inhibitory concentrations of antibiotics, the strongest impact on mutagenesis was tetracycline, trimethoprim, and cefotaxime among A. hydrophila, whereas ciprofloxacin and trimethoprim were most influential among A. caviae populations. Although majority of the antimicrobials appear to lose their effect at 0.25X of the MIC value, trimethoprim impacted mutation frequencies as low as 0.0078X the MIC (0.156 µg/mL). Common wastewater disinfectants also accelerated the presence of specific mutations in A. caviae. Together, although wastewater treatment is instrumental in reducing microbial populations, as well as resistant populations, our findings demonstrate the potential impact wastewater and its disinfectants have on the evolution of antimicrobial resistance and virulence.
Keywords: Aeromonas; Antibiotic resistance; Evolution; Mutation freqeuncy; Mutations; Wastewater